Structural and functional analysis of the Helicobacter pylori lipoprotein chaperone LolA - Jaiman, Deepika; Persson, Karina (Frontiers in Microbiology, 2024)
Lipoproteins are crucial for maintaining the structural integrity of bacterial membranes. In Gram-negative bacteria, the localization of lipoprotein (Lol) system facilitates the transport of these proteins from the inner membrane to the outer membrane. In Helicobacter pylori, an ε-proteobacterium, lipoprotein transport differs significantly from the canonical and well-studied system in Escherichia coli, particularly due to the absence of LolB and the use of a LolF homodimer instead of the LolCE heterodimer. This study presents the crystal structure of the H. pylori lipoprotein chaperone LolA (LolA-HP) and its interaction with lipopeptide antibiotics such as polymyxin B and colistin. Isothermal titration calorimetry revealed that, unlike LolA from Vibrio cholerae and Porphyromonas gingivalis, LolA-HP does not bind to these antibiotics. Structural comparisons showed that LolA-HP has a deeper hydrophobic cleft but lacks the negative electrostatic potential critical for binding polymyxins. These findings offer insights into the structural diversity of LolA across bacterial species and its potential as a target for antibacterial agents.